Post-flânerie: How do mobile devices shape the experience of the city? - Argin, Gorsev; Pak, Burak; Turkoglu, Handan (SHS web of conferences, 2019)
In the last decade, the advances in mobile technologies and location-based applications reshaped our mutual relationship with the urban environment. These technologies, as both a mean and barrier to the engagement between humans and their environment, have transformed the urban experience in profound ways. Urban experience is a relatively new concept introduced with the rise of modern cities in the nineteenth century. Its loss due to the rapid urbanization has been a subject of debate since then. Among the discussions that take place in this debate, the figure of ‘flâneur’ plays an extensive role. The flâneur is a figure who wanders through and appropriates the metropolitan city in pursuit of urban experience and reaps aesthetic meaning from the spectacle of the teeming crowds. Flânerie, or the act of wandering, and its implications for our understanding of urban life have been profound. Today, mobile technologies create a new kind of urban wanderer which is described as “post-flâneur”. In this paper, by examining the altering concept of flânerie, we discuss the effects of mobile technologies on urban experience. Based on an informed study of a wide range of theories, we make reflections on the impact of mobile devices on the mutual relationship between humans and their environment, introduce key concepts for understanding the emergent phenomenon of post-flânerie and elaborate on its interconnections with the phenomena of cyber and hybrid-flânerie.